Evolution of Innate and Adaptive Effector Cell Functions during Acute HIV-1 Infection - Alter, Galit; Teigen, Nickolas; Ahern, Ryan; Streeck, Hendrik; Meier, Angela; Rosenberg, Eric S.; Altfeld, Marcus (The Journal of infectious diseases, 2007)
Early events during acute human immunodeficiency virus type 1 (HIV-1) infection are critical in determining the course of disease progression. Cells of the innate and adaptive immune responses are involved in this acute response to infection; however, little is known about the coevolution of innate and adaptive effector cell populations during the initial phase of HIV-1 infection. Here, we have characterized the development of innate natural killer (NK) cell and adaptive HIV-1-specific CD8+ T cell function during acute HIV-1 infection. Although NK cell populations were significantly expanded during acute infection before HIV-1 seroconversion, HIV-1-specific CD8+ T cell responses were absent or weak and were inversely correlated with the level of NK cell activity. NK cell activity was directly correlated with the level of viral replication during acute HIV-1 infection and declined rapidly in subjects who initiated highly active antiretroviral therapy, whereas NK cell activity remained elevated in subjects who did not initiate therapy. Yet, reexposure to HIV-1 antigen during treatment discontinuation in chronic infection resulted in a synchronous increase in NK and CD8+ T cell activity. Overall, these data demonstrate that expansion of the NK cell population precedes the development of adaptive HIV-1-specific CD8+ T cells during acute infection but that both effector cell subsets respond with similar kinetics during chronic HIV-1 infection.